Two new fish species of the subfamily Anthiinae (Perciformes, Serranidae) from the Marquesas - Williams, Jeffrey T.; Delrieu-Trottin, Erwan; Planes, Serge (Zootaxa, 2013)
Two new species of anthiine fishes are described from the Marquesas Islands, French Polynesia. Plectranthias flammeus was found at depths from 20–45 m and is characterized by dorsal rays X, 14 or 15, with spines 1–6 bearing fleshy white tabs at their tips, longest fleshy tab on spine 4; 14 unbranched pectoral rays; lateral line incomplete with 16–17 tubed scales; preopercle with 8–10 small spines along posterior margin and 2 antrorse spines on ventral margin; broad, fiery red-orange streak across lower cheek; head and body with irregularly spaced maroon-ringed yellow blotches on a white back-ground; pair of small dark oblong spots (red with black centers in life) on the bases of the middle rays of the caudal fin. Pseudanthias oumati was found on the outer reef slope of Fatu Hiva at a depth of 50–55 m and is characterized by 3rd dorsal spine elongate and tipped with fleshy yellow filament extending beyond tip of spine; lateral-line scales 43; gill rak-ers 10 + 28; no papillae on posterior edge of orbit; front of upper lip not thickened (male condition unknown); caudal fin lunate; color of female yellow, all fins yellow with narrow magenta margin (except pectoral fin, which lacks magenta); no stripe from snout to pectoral base; small scales located on basal quarter of soft-dorsal fin from segmented rays 1–12; dorsal profile of head slightly concave.